Photoionization of [Formula: see text] Isomers. Unimolecular and Bimolecular Reactions of the [Formula: see text] Ions - Sieck, L. W. (J Res Natl Bur Stand A Phys Chem, 1972)
1-Butene, cis-2-butene, isobutene and methylcyclopropane have been photoionized with the resonance lines of krypton (10.0–10.6 eV) and argon (11.6–11.8 eV). We have determined that the internally excited [Formula: see text] ion and, to a much lesser extent, the [Formula: see text] ion isomerizes to the [Formula: see text] structure. In both cases the extent of isomerization increases, approximately by a factor of ten when the photon energy is increased from 10 to 11.7 eV. An inert gas, neon, quenches the isomerization of the [Formula: see text] ion and, to a much lesser rextent, that of the [Formula: see text] ion. The unimolecular fragmentation of the [Formula: see text] isomeric ions has been examined at 11.61–11.8 eV. In this energy range the dissociative lifetime of [Formula: see text] was found to be at least 5 × 10(−6) s, and collisional quenching of the dissociative process is already noticeable at pressures in the 10(−3) torr range. The rate coefficients for the reaction [Formula: see text] occurring in the isomeric C(4)H(8) systems have been determined under conditions where the structure of the reacting [Formula: see text] ion is established. The values in cm(3)/molecule · second are 1-C(4)H(8) − 6.0 ± 0.5 × 10(−l0), cis-2-C(4)H(8) − 0.37 ± 0.1 × 10(−10), i-C(4)H(8) − 5.4 ± 0.4 × 10(−10). At pressure below 10(−3) torr, the internally excited [Formula: see text] produced in the reaction dissociates along various channels with relative probabilities depending upon the structure of both the ionic and neutral reactant. Above 10(−3) torr collisional quenching of [Formula: see text] is noted.